1993
DOI: 10.1111/j.1525-1446.1993.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes and Coping Patterns Among Caregivers of Stroke Survivors

Abstract: Although caregiving has been a major focus for research, little is known about the day-to-day changes in lifestyle faced by caregivers. Yet lifestyle, developed over time, manifests an individual's very identity. Using a multimethod approach, we assessed the perceptions of lifestyle changes and coping patterns of 20 caregivers of first-time stroke survivors in the early poststroke period. An outcome-oriented matrix was employed for qualitative analysis, and findings were expanded by additional quantitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 9 publications
3
34
0
8
Order By: Relevance
“…Carers feel ill prepared for their role and have concerns about their own competence. 90 -92 Caregiving can result in lifestyle changes 89,93 as well as physical, emotional, and financial problems. 90,94 -96 It was also reported that carers feel isolated, that their own needs are neglected, 91 and that family relationships can suffer.…”
Section: Mckevitt Et Al Qualitative Studies Of Stroke: a Systematic Rmentioning
confidence: 99%
“…Carers feel ill prepared for their role and have concerns about their own competence. 90 -92 Caregiving can result in lifestyle changes 89,93 as well as physical, emotional, and financial problems. 90,94 -96 It was also reported that carers feel isolated, that their own needs are neglected, 91 and that family relationships can suffer.…”
Section: Mckevitt Et Al Qualitative Studies Of Stroke: a Systematic Rmentioning
confidence: 99%
“…Os cuidadores de pessoas com AVC vivenciam mudanças no estilo de vida (16) que reduzem (17) , modificam (12) e geram insatisfações na vida social dos mesmos (18) , devido às condições limitantes impostas pela doença, trazendo sentimentos de isolamento (19) e proporcionado relacionamento mais próximo e circunscrito às atividades domésticas (20) .…”
Section: Aspectos Gerando Sobrecarga O Isolamento Socialunclassified
“…O acúmulo de atividades de trabalho com as tarefas de casa (12) faz com que os cuidadores sintam-se ocupados (6) , experienciando limitação do tempo livre, como conseqüência direta por estarem assumindo o cuidado do ente (14,16) .…”
Section: Os Fatores Limitantes Da Vida Social Do Cuidador São Mostradunclassified
“…A previously dependent spouse may have to adjust to the role of deaUng with aU busmess and finance at the same time as encouraging an unhappy spouse (Holbrook, 1982). Changes to estabUshed pattems of daily Ufe can represent a major strain for carers (Periard and Ames, 1993). QuaUtative American studies of the effects of stroke on wives of stroke patients have demonstrated the unfamUiar new responsibUities of role changes, m addition to caring for the stroke patient (Rosenthal et al, 1993;Enterlante and Keme, 1995;Robinson-Smith and Mahoney, 1995).…”
Section: Adjustmentmentioning
confidence: 99%